Successful treatment of "accelerated" chronic lymphocytic leukemia with single agent ibrutinib: A report of two cases. (2021) - Xie, John; Jang, Albert; Vegel, Andrew; Hajja, Yasmin; Mouawad, Yara; Baghian, Ali; Berbari, Bachir; Schmid, Janet L.; Socola, Francisco; Safah, Hana; Saba, Nakhle S.
Abstract: "Accelerated" chronic lymphocytic leukemia/small lymphocytic lymphoma (A-CLL) is a rare histological variant of CLL/SLL, which tends to exhibit an aggressive clinical behavior compared to CLL. Due to the rarity of A-CLL (<1% of all cases), the optimal management remains ill-defined. We report two cases of A-CLL from our institution, in which both relapsed following initial chemoimmunotherapy regimens. Both patients were treated with single agent ibrutinib, a Bruton's tyrosine kinase inhibitor (BTKi), and achieved rapid, deep and durable responses. With the absence of clear guidance on A-CLL treatment, BTKi agents should be considered in the frontline treatment of A-CLL.